2020
DOI: 10.1007/s00384-020-03696-7
|View full text |Cite|
|
Sign up to set email alerts
|

Modified two-stage restorative proctocolectomy with ileal pouch-anal anastomosis for ulcerative colitis: a systematic review and meta-analysis of observational research

Abstract: Purpose: Restorative proctocolectomy(RPC) is performed for patients with refractory ulcerative colitis(UC). This operation is performed in 2 or 3-stages and involves forming a diverting loop ileostomy thought to protect patients from complications related to anastomotic leak. However, some advocate for a modified 2-stage approach, consisting of subtotal colectomy followed by completion proctectomy and ileal pouch anal anastomosis without diverting ileostomy. We present a systematic review and meta-analysis com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Zooming in on keywords frequently used by authors in Table 7 , interesting trends, and the future of evidence synthesis emerged, including lines of research on: 1) identification of risk factors, surveillance methods, and surveillance intervals for UC-associated colorectal cancer ( Hata et al, 2019 ; Zhou et al, 2019 ; Zhang and Gan, 2021 ); 2) anti-TNF drugs for UC induction of remission and maintenance therapy ( Guo et al, 2019 ; Vande Casteele et al, 2019 ); 3) surgical treatment of UC which include proctocolectomy with ileal pouch–anal anastomosis ( Drews et al, 2019 ; Luo et al, 2020 ); 4) dysbiosis of the gut microbiota (predominantly bacteria) in the pathogenesis of UC and FMT as a therapeutic strategy for UC ( Blanchaert et al, 2019 ; Khan et al, 2019 ; Guo et al, 2020 ; Liu et al, 2021 ); 5) diagnostic criteria and differential diagnoses for UC ( Smith et al, 2020 ; Wang et al, 2021 ); 6) NF-κB signaling pathway in the pathogenesis of UC and its clinical implication ( Lu and Zhao, 2020 ; Dejban et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zooming in on keywords frequently used by authors in Table 7 , interesting trends, and the future of evidence synthesis emerged, including lines of research on: 1) identification of risk factors, surveillance methods, and surveillance intervals for UC-associated colorectal cancer ( Hata et al, 2019 ; Zhou et al, 2019 ; Zhang and Gan, 2021 ); 2) anti-TNF drugs for UC induction of remission and maintenance therapy ( Guo et al, 2019 ; Vande Casteele et al, 2019 ); 3) surgical treatment of UC which include proctocolectomy with ileal pouch–anal anastomosis ( Drews et al, 2019 ; Luo et al, 2020 ); 4) dysbiosis of the gut microbiota (predominantly bacteria) in the pathogenesis of UC and FMT as a therapeutic strategy for UC ( Blanchaert et al, 2019 ; Khan et al, 2019 ; Guo et al, 2020 ; Liu et al, 2021 ); 5) diagnostic criteria and differential diagnoses for UC ( Smith et al, 2020 ; Wang et al, 2021 ); 6) NF-κB signaling pathway in the pathogenesis of UC and its clinical implication ( Lu and Zhao, 2020 ; Dejban et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…While there is a paucity of a highquality prospective data comparing modified 2-stage to other approaches, a recent meta-analysis demonstrated that there was an increase in anastomotic leaks in pediatric patients undergoing a modified 2-stage approach when compared to the 3-stage approach. It also showed a lower leak rate in comparison to traditional 2-stage IPAA in patients with increasing exposure to biologics [55]. Large prospective data is still needed to truly assess the utility of this approach.…”
Section: Surgical Techniquesmentioning
confidence: 92%
“…A meta-analysis comparing outcome in 10 observational studies including 1,727 patients found the modified twostage approach to have a lower leak rate than the classic twostage approach in adult patients (p <0.001), possibly associated with a lower preoperative use of biologics. 66 In pediatric patients, however, the modified two-stage approach had a higher rate of anastomotic leak than the three-stage approach (p ¼ 0.03). 66 A very interesting on-going trial is the randomized multicenter IDEAL trial initiated by the French group GETAID Chirurgie, comparing modified two-stage and three-stage IPAA.…”
Section: Available Comparisons On Staged Proceduresmentioning
confidence: 93%
“…66 In pediatric patients, however, the modified two-stage approach had a higher rate of anastomotic leak than the three-stage approach (p ¼ 0.03). 66 A very interesting on-going trial is the randomized multicenter IDEAL trial initiated by the French group GETAID Chirurgie, comparing modified two-stage and three-stage IPAA. 67 The completion of this study will hopefully increase the knowledge on how to deal with these patients in the future.…”
Section: Available Comparisons On Staged Proceduresmentioning
confidence: 93%